Inset feed for antenna miniaturisation - Esa, Mazlina; Subahir, Suhaila; Ahmad, Norul Husna; Yusof, Sharifah Kamilah (Penerbit UTM Press, 2000)
An experimental investigation of a rectangular microstrip patch structure having an inset or recessed feed at its non-radiating edge is presented. The basic structure operates at 1.6 GHz, when fed with a coaxial line or microstrip side feed line. However, the inset fed structure operates at a lower frequency of 1.35 GHz. The antenna does not need any impedance matching network. The well-matched antenna exhibits similar performance to that of the basic structure. The inset feed structure behaves like a matching line as well as miniaturising the physical antenna structure.